METODE MEMBACA SAS (STRUKTURAL ANALITIK SINTETIK) DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN DI KELAS I SDN 79 PEKANBARU - Otang Kurniaman; Eddy Noviana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research using the experiment quasi carried out in the class 1 SDN 79 Pekanbaru by comparing the skill read beginning between the kontrol and class experiment. The result of the data pre educational the result of the average blended class eksperiment 70,26 and the class kontrol with the averageb 72,76 be seen from the test then summed there is not different the significant because X count = 1,39 < X table = 5, 991. In the data post educational blended class experiment 84,43 and the class kontrol 79,50 on the test the differences there are significant different between the experiment and class kontrol because Xcount = 6,40 > Xtable = 5,991. In an increase in the experiment test with N gain 0,48 with the medium categories and the class kontrol with N gain 0,25 the low categories it gives an idea that SAS methode more effective in improving read the beginning.